1997
DOI: 10.1016/s0896-6273(00)80310-4
|View full text |Cite
|
Sign up to set email alerts
|

(S)NO Signals: Translocation, Regulation, and a Consensus Motif

Abstract: metals in all biological systems (Stamler, 1994). The S-nitrosothiol (SNO) and metal nitrosyl (MNO) products and Nikolaus J. Sucher ‡ § have intrinsic reactivities that enable local action. The * Departments of Medicine, Cell Biology, NO group is transferred by covalent exchange mecha- † Chemistry and Biochemistry nisms including thiol/nitrosothiol (RSNO/R'S Ϫ ⇔ R'SNO/ Duke University RS Ϫ ) or nitrosothiol/metal (SNO/M ⇔ MNO/S) exchange. Durham, North CarolinaThis mode of intra-and intercellular communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
496
1
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 661 publications
(516 citation statements)
references
References 54 publications
13
496
1
6
Order By: Relevance
“…In general, a consensus motif of amino acids comprised of nucleophilic residues (generally an acid and a base) surround a critical cysteine, which increases the cysteine sulfhydryl's susceptibility to S-nitrosylation. 46,47 Our group first identified the physiological relevance of S-nitrosylation by showing that NO and related RNS exert paradoxical effects via redox-based mechanisms -NO is neuroprotective via S-nitrosylation of NMDA receptors (as well as other subsequently discovered targets, including caspases), and yet can also be neurodestructive by formation of peroxynitrite (or, as later discovered, reaction with additional molecules such as parkin, PDI, GAPDH, and MMP-9) (Figure 1). 6,8,9,12,14,16,17,[19][20][21][22]48 Over the past decade, accumulating evidence has suggested that S-nitrosylation can regulate the biological activity of a great variety of proteins, in some ways akin to phosphorylation.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
“…In general, a consensus motif of amino acids comprised of nucleophilic residues (generally an acid and a base) surround a critical cysteine, which increases the cysteine sulfhydryl's susceptibility to S-nitrosylation. 46,47 Our group first identified the physiological relevance of S-nitrosylation by showing that NO and related RNS exert paradoxical effects via redox-based mechanisms -NO is neuroprotective via S-nitrosylation of NMDA receptors (as well as other subsequently discovered targets, including caspases), and yet can also be neurodestructive by formation of peroxynitrite (or, as later discovered, reaction with additional molecules such as parkin, PDI, GAPDH, and MMP-9) (Figure 1). 6,8,9,12,14,16,17,[19][20][21][22]48 Over the past decade, accumulating evidence has suggested that S-nitrosylation can regulate the biological activity of a great variety of proteins, in some ways akin to phosphorylation.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
“…NO can produce both single cysteine S-nitrosylations as in case of Ha-Ras (Lander et al, 1997), caspase 3 (Rossig et al, 1999), and nuclear factor-kappa B (Marshall and Stamler, 2001) and multiple cysteine S-nitrosylations in case of Nethylmaleimide Sensitive Factor (NSF) (Matsushita et al, 2003) and the ryanodine receptor (Voss et al, 2004). Consensus S-nitrosylation motifs have been postulated by Stamler et al (1997). These motifs have been suggested to contain hydrophilic residues adjacent to the specific cysteine either in the primary structure (Stamler et al, 1997) or brought together by three-dimensional (3D) conformations (Ascenzi et al, 2000(Ascenzi et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Consensus S-nitrosylation motifs have been postulated by Stamler et al (1997). These motifs have been suggested to contain hydrophilic residues adjacent to the specific cysteine either in the primary structure (Stamler et al, 1997) or brought together by three-dimensional (3D) conformations (Ascenzi et al, 2000(Ascenzi et al, , 2001. However, our previous studies, utilizing short peptide sequences, suggested that S-nitrosylation may be independent of the amino acids surrounding the cysteine residue.…”
Section: Introductionmentioning
confidence: 99%
“…Kinases are often co-localised with their substrates, with additional selectivity achieved by consensus motifs in the primary sequence of a target protein that is phosphorylated. Similarly, targets of S-nitrosation can localise with NO synthase (NOS) enzymes [8], and may contain linear amino acid consensus motifs [23], thus mirroring key features of kinase-mediated phosphorylation. Furthermore, denitrosylase enzymes that remove NO from proteins are described to play the corresponding role of phosphatases in phospho-regulated proteins [22].…”
Section: Stable Protein S-nitrosation As a Regulatory End-effector Mementioning
confidence: 99%
“…Indeed, a consensus motif for S-nitrosation was proposed in 1994 when it was found that many protein S-nitrosothiols have basic or acidic amino acid preceding the cysteine followed by an acidic amino acid [55]. From this a consensus motif consisting of a core of three residues (K/R/H/D/E)-C-(D/E) was proposed to predict S-nitrosation in hydrophobic protein domains [23]. The computational prediction software GPS-SNO (http://sno.biocuckoo.org/) was used to analyze 467 experimentally verified S-nitrosothiol sites in 302 proteins, to develop algorithms that computationally 'predict' Snitrosation from a primary sequence alone.…”
Section: A Consensus Motif For Selective and Targeted Protein S-nitromentioning
confidence: 99%